The Influence of Company Growth, Capital Structure, and Liquidity on Earnings Response Coefficient (A Study of Food and Beverage Sub Sector Companies Listed on the Indonesia Stock Exchange from 2019 to 2023) - Prayoga, Wahyu Imam; Parwati, Ni Made Suwitri; Mile, Yuldi; Pakawaru, Muhammad Ilham (Accounting Studies and Tax Journal (COUNT), 2025)
This study aims to determine and analyze the effect of company growth, capital structure, and liquidity on ERC. This type of research is quantitative research with secondary data sources for 2019-2023 obtained from the official IDX and Yahoo Finance websites. The sampling technique used the purposive sampling method with a sample of 27 companies from 95 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023. The data analysis used was multiple linear regression analysis with the help of SPSS version 25. The results of the study showed that (1) company growth had a positive and significant effect on the earnings response coefficient; (2) Capital structure had a significant negative effect on the earnings response coefficient; (3) liquidity has a significant positive effect on the earnings response coefficient.